2019
DOI: 10.1016/j.atmosenv.2018.11.058
|View full text |Cite
|
Sign up to set email alerts
|

Improving indoor air quality, health and performance within environments where people live, travel, learn and work

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(105 citation statements)
references
References 208 publications
1
76
0
4
Order By: Relevance
“…A strong focus on atmospheric air pollution has been developed worldwide which has led to a significant reduction of some contaminants in the atmospheric environment. The starting point of this approach is that the population, especially in urban areas, spends most of the time (up to 90 %) indoors (Carrer et al, 2000;Avino et al, 2003;Kelly & Fussell, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A strong focus on atmospheric air pollution has been developed worldwide which has led to a significant reduction of some contaminants in the atmospheric environment. The starting point of this approach is that the population, especially in urban areas, spends most of the time (up to 90 %) indoors (Carrer et al, 2000;Avino et al, 2003;Kelly & Fussell, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many studies showed a higher toxicity for cigarette smoke compared with ambient PM sources such as dust and traffic. [64][65][66] To improve indoor air quality for people especially for vulnerable groups, 67 SHS is still an important pollutant from a public health perspective. 1,20 Peak analysis developed in this study allows us to quantify the contribution of PM 2.5 from SHS exposure from specific locations and time periods.…”
Section: Discussionmentioning
confidence: 99%
“…As pollutants from exterior sources can affect the interior air quality [22][23], the residential spaces (RS) that were investigated from the point of view of indoor air quality were selected based on the area where they are located, being selected a building located relatively far from the traffic (RS1) and a building located next to a high traffic boulevard (RS2 and RS3). Interior spaces (with drawings in fig.3) were chosen on the assumption that in the kitchen areas there are many sources of emissions and the resting area (bedroom) is the most importance space, where emissions should be minimized.…”
Section: Fig1 Locations Of the Monitored Spaces From Bucharest Citymentioning
confidence: 99%
“…Most of the times the effects of VOCs on human health are amplified by indoor conditions such as temperature and humidity [21]. VOCs could be at the base of various discomforts inside the buildings and lead to what is called sick building syndrome (SBS) in scientific literature [4,22]. Understanding the evolution of TVOCs concentration inside buildings is the basis for predicting this variation and a correct ventilation strategy for interior spaces.…”
mentioning
confidence: 99%